Method for nondestructive testing of relative dielectric constant of piezoelectric material

Through X-ray diffraction technology, the proportion of the crystal surface diffraction peak intensity of PZT piezoelectric materials is measured, and its relative dielectric constant is calculated, which solves the problems of cumbersome detection and damage pollution in the existing technology, and achieves fast and accurate dielectric constant detection. and uniformity assessment.

CN119290983APending Publication Date: 2025-01-10SHENGLAN SEMICON (CHANGZHOU) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411526183.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing testing methods require the preparation of electrodes to detect the relative dielectric constant of PZT piezoelectric wafers. The process is cumbersome and easy to cause damage and pollution, affecting the testing efficiency and accuracy.

Method used

X-ray diffraction technology is used to measure the proportion of diffraction peak intensity of different crystal surfaces of piezoelectric materials, calculate the weighted average value of the theoretical dielectric constant of each crystal surface, and obtain the relative dielectric constant of the piezoelectric material to achieve no damage and pollution-free detection.

Benefits of technology

Fast, efficient and damage-free relative dielectric constant detection is achieved, which reduces detection costs, improves detection efficiency, and can evaluate the in-plane distribution uniformity of dielectric constants, with an error of less than 5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290983A_ABST
    Figure CN119290983A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of testing. The invention provides a method for non-destructively testing the relative dielectric constant of a piezoelectric material, which is characterized in that different crystal faces (orientation distribution) contributing to the relative dielectric constant in the piezoelectric material are obtained by means of X-ray diffraction, and the relative dielectric constant of the piezoelectric material is measured by taking the diffraction peak intensity proportions of the crystal faces as weights. And calculating the weighted average of the theoretical dielectric constants of the crystal faces to obtain the relative dielectric constant of the piezoelectric material. According to the method, the test speed is high, an electrode does not need to be prepared, each test point can be completed within 1 min as soon as possible, the piezoelectric material is not damaged or polluted, meanwhile, the relative dielectric constants at different positions on the whole piezoelectric wafer can be conveniently tested, and then the distribution uniformity of the relative dielectric constants in the plane is evaluated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of testing technology and relates to a method for non-destructively testing the relative dielectric constant of a piezoelectric material. Background Art

[0002] With the rapid development of micro-electromechanical systems (MEMS) technology, piezoelectric materials are increasingly used in various sensors and actuators. Lead zirconate titanate (PZT), as a material with excellent piezoelectric properties, has shown great application potential in the field of piezoelectric MEMS devices in recent years. In particular, the wide application of PZT piezoelectric wafers (films) in fingerprint recognition, ultrasonic imaging, distance sensing and other fields has made it one of the hot topics in MEMS research.

[0003] When PZT piezoelectric wafers are used in MEMS sensing applications, their key performance indicators mainly include the piezoelectric constant e 31 and relative dielectric constant ε r . These performance indicators have a direct impact on the sensing performance of the device. The piezoelectric constant indicates the strain generated by the material under a unit electric field. It is an important parameter for measuring the piezoelectric effect of the material. Generally, the larger the piezoelectric constant, the stronger the piezoelectric effect of the material and the higher the sensitivity of the sensor. The relative dielectric constant indicates the degree of polarization of the material under the action of the electric field. It is an important parameter for measuring the dielectric properties of the material. Generally, the lower the relative dielectric constant, the weaker the charge storage capacity of the material and the faster the response speed of the sensor. That is, the sensing performance is proportional to the piezoelectric constant and inversely proportional to the relative dielectric constant. The larger the piezoelectric constant and the lower the relative dielectric constant, the higher the sensing performance. Based on this rule, in order to ensure device performance, PZT piezoelectric wafers usually need to evaluate the relative dielectric constant before the tape-out process.

[0004] At present, the commonly used method for testing the relative dielectric constant is the parallel plate capacitor method. The basic principle of this method is to plate a layer of top electrode and bottom electrode (i.e., bottom electrode / PZT / top electrode) on both sides of the PZT wafer to form a parallel plate capacitor similar to a "sandwich" form, and measure the capacitance value of the flat plate capacitor through an LCR dielectric tester to calculate the relative dielectric constant. However, although this method can obtain the relative dielectric constant of the piezoelectric wafer more accurately, it requires the piezoelectric wafer to have both a top electrode and a bottom electrode, and in most cases the wafer needs to be cut, etched, and other processes. On the one hand, there are many process steps in the early stage, which increases the complexity and reduces the test efficiency; on the other hand, these processing techniques are prone to cause irreversible damage and contamination to the piezoelectric wafer, which is a kind of lossy test.

[0005] Therefore, it can be seen from the above that the development of a fast, efficient, non-destructive and non-polluting detection method is of great practical significance for promoting the application and development of piezoelectric materials such as PZT piezoelectric wafers. Summary of the invention

[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for non-destructively testing the relative dielectric constant of piezoelectric materials, wherein the method uses the means of X-ray diffraction to obtain different crystal planes (orientation distribution) in the piezoelectric material that contribute to the relative dielectric constant, and the weighted average value of the theoretical dielectric constant of each crystal plane is calculated by taking the diffraction peak intensity ratio of these crystal planes as the weight, and obtaining the relative dielectric constant of the piezoelectric material. The method has a fast test speed, does not require the preparation of electrodes, and each test point can be completed within 1 minute at the fastest, and does not damage or pollute the piezoelectric material. At the same time, it is convenient to test the relative dielectric constant at different positions on the entire piezoelectric wafer, and then evaluate the distribution uniformity of the relative dielectric constant in the plane.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for non-destructively testing the relative dielectric constant of a piezoelectric material, comprising the following steps:

[0009] Perform an X-ray diffraction test on the piezoelectric material to be tested, determine the phase that contributes to the relative dielectric constant, obtain the diffraction peak intensity of each crystal plane of the phase, sum up to obtain the total diffraction peak intensity, and then calculate the diffraction peak intensity ratio of each crystal plane;

[0010] The weighted average of the theoretical dielectric constants of each crystal plane is calculated using the diffraction peak intensity ratio of the crystal plane as the weight to obtain the relative dielectric constant of the piezoelectric material to be tested.

[0011] The specific implementation of the method described in the present invention is based on the following assumptions: First, piezoelectric materials with a single orientation have a fixed dielectric constant, and there are differences in the values ​​between piezoelectric materials with different single orientations; second, in piezoelectric materials with multiple orientations (such as polycrystalline PZT films), the contribution of each orientation to the dielectric constant is independent of each other and does not affect each other; third, in piezoelectric materials with multiple orientations, the contribution value of each orientation to the dielectric constant is proportional to its proportion. Therefore, it is only necessary to know the proportion of the contribution phases of different orientations in the piezoelectric material to deduce the overall relative dielectric constant. In the present invention, this proportion ratio value is calculated by the proportion of the diffraction peak intensity of different crystal planes obtained by XRD testing.

[0012] It should be noted that the values ​​of diffraction peak intensity of different crystal planes (orientations) must be obtained from the same sample in the same test, because different batches of samples and different batches of test conditions have an impact on the absolute value of the diffraction peak intensity. The absolute values ​​of the diffraction peak intensity of the same crystal plane are not comparable, but the calculated proportion of the diffraction peak intensity is comparable and accurate.

[0013] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] As a preferred technical solution of the present invention, a method for obtaining the theoretical dielectric constant of a crystal plane includes:

[0015] In the piezoelectric material to be tested, determining the crystal planes used for calculation and the total number of crystal planes, and selecting a standard piezoelectric material corresponding to the total number;

[0016] Performing an X-ray diffraction test on each of the standard piezoelectric materials to obtain the diffraction peak intensity of the corresponding crystal plane, summing up the total diffraction peak intensity, and then calculating the diffraction peak intensity ratio of the crystal plane;

[0017] Using a parallel plate capacitor method, testing the standard relative dielectric constant of each of the standard piezoelectric materials;

[0018] Taking the diffraction peak intensity ratio of the crystal plane as the weight, the obtained standard relative dielectric constant as the dependent variable, and the theoretical dielectric constant of the crystal plane as the independent variable, the weighted average calculation equation group of the independent variables is listed, and the equations are solved simultaneously to obtain the theoretical dielectric constant of the crystal plane.

[0019] In the present invention, further, multiple groups of measurements and calculations can be performed, and at least two groups of weighted average calculation equations can be listed to evaluate the theoretical dielectric constant (theoretical value of the relative dielectric constant), and then the average value can be taken to obtain data results that are closer to the actual value.

[0020] It should be noted that when there is only one phase in the standard piezoelectric material and the phase has only one orientation, the standard relative dielectric constant measured by the parallel plate capacitor method can be directly used as the theoretical dielectric constant of the orientation.

[0021] As a preferred technical solution of the present invention, the parallel plate capacitor method includes:

[0022] Bottom electrodes and top electrodes are prepared on both sides of the standard piezoelectric material to form a parallel plate capacitor. The capacitance value C of the obtained parallel plate capacitor is tested, and then the standard relative dielectric constant is calculated according to the following formula:

[0023] C=(ε0×ε r ′×S) / d;

[0024] Where C is the capacitance value, unit F; ε0 is the vacuum dielectric constant, ε0 = 8.85 × 10 -12 F / m; ε r' is the standard relative dielectric constant; S is the electrode area, calculated based on the smaller area of ​​the bottom electrode and the top electrode, in m 2 ; d is the thickness of the standard piezoelectric material, unit: m.

[0025] As a preferred technical solution of the present invention, the test frequency of the parallel plate capacitor method is 1kHz to 1MHz, for example, 1kHz, 3kHz, 5kHz, 8kHz, 10kHz, 25kHz, 50kHz, 80kHz, 100kHz, 200kHz, 300kHz, 400kHz, 500kHz, 600kHz, 700kHz, 800kHz, 900kHz or 1MHz, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are equally applicable.

[0026] As a preferred technical solution of the present invention, the lowest index crystal plane in at least one crystal plane cluster in the phase is selected as the effective crystal plane, and only the effective crystal plane is used for calculation.

[0027] Taking the PZT piezoelectric wafer as an example, the orientations of the wafer (100) and (200) and their contributions to the dielectric constant are equivalent. Therefore, when calculating, it is only necessary to include them in the (100) orientation and use the diffraction peak intensity of (100) for calculation. Similarly, (100), (001) and (010) are also equivalent. Therefore, one of the lowest index crystal planes of each crystal plane cluster can be used as the effective crystal plane for subsequent calculations.

[0028] As a preferred technical solution of the present invention, the number of types of the crystal face clusters is 1, 2, 3 or 4.

[0029] As a preferred technical solution of the present invention, the piezoelectric material to be tested includes a thin film or wafer of polycrystalline lead zirconate titanate; the thickness of the piezoelectric material to be tested is 0.1μm to 2μm, for example, 0.1μm, 0.3μm, 0.5μm, 0.8μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm or 2μm, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0030] As a preferred technical solution of the present invention, the piezoelectric material to be tested is a film or wafer of polycrystalline lead zirconate titanate, and the contributing phase is a perovskite phase.

[0031] As a preferred technical solution of the present invention, the crystal planes of the perovskite phase include (100), (110), (111) and (211).

[0032] In the present invention, for the PZT piezoelectric wafer, the main orientations include the perovskite phase (100), (110), (111), (211) and the pyrochlore phase. Among them, the relative dielectric constant of the PZT material in the pyrochlore phase is extremely low, and the pyrochlore phase is not a phase that is desired to appear in actual production and application. Therefore, in the present invention, the relative dielectric constant of the pyrochlore phase is ignored, and only four perovskite phases (100), (110), (111), (211) are considered.

[0033] As a preferred technical solution of the present invention, the following steps are included:

[0034] A polycrystalline lead zirconate titanate film or wafer with a thickness of 0.1 μm to 2 μm is used as a piezoelectric material to be tested, and an X-ray diffraction test is performed on the piezoelectric material to be tested; the phase that contributes to the relative dielectric constant of the piezoelectric material to be tested is determined to be a perovskite phase, and the crystal planes (100), (110), (111) and (211) of the perovskite phase are used as effective crystal planes, and other crystal planes of the perovskite phase and the crystal planes of the pyrochlore phase are not calculated. The diffraction peak intensity of each effective crystal plane is obtained, and after the total diffraction peak intensity is obtained by summing, the diffraction peak intensity ratio of each effective crystal plane is calculated according to the following formula:

[0035]

[0036] Among them, R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl); P (hkl) is the diffraction peak intensity of the crystal plane (hkl); P (100) , P (110) , P (111) and P (211) are the diffraction peak intensities of the crystal planes (100), (110), (111) and (211);

[0037] Taking the diffraction peak intensity ratio of the effective crystal plane as the weight, the weighted average of the theoretical dielectric constant of each effective crystal plane is calculated according to the following formula:

[0038] ε r =∑R (hkl) *ε (hkl) ;

[0039] Among them, ε r is the relative dielectric constant; ε (hkl) represents the theoretical dielectric constant of the crystal plane (hkl); R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl);

[0040] Get the relative dielectric constant ε of the piezoelectric material to be tested r .

[0041] The method for obtaining the theoretical dielectric constant of the effective crystal plane includes:

[0042] In the piezoelectric material to be tested, determining the effective crystal planes and the total number of effective crystal planes used for calculation, and selecting a standard piezoelectric material corresponding to the total number;

[0043] Performing an X-ray diffraction test on each of the standard piezoelectric materials to obtain the diffraction peak intensity of the effective crystal plane, summing up the total diffraction peak intensity, and then calculating the diffraction peak intensity ratio of the effective crystal plane;

[0044] Bottom electrodes and top electrodes are prepared on both sides of the standard piezoelectric material to form a parallel plate capacitor. The parallel plate capacitor method is used with a test frequency of 1kHz to 1MHz. The capacitance value C of the parallel plate capacitor obtained is tested, and then the standard relative dielectric constant of each standard piezoelectric material is calculated according to the following formula:

[0045] C=(ε0×ε r '×S) / d;

[0046] Where C is the capacitance value, unit F; ε0 is the vacuum dielectric constant, ε0 = 8.85 × 10 -12 F / m; ε r ' is the standard relative dielectric constant, unit F / m; S is the electrode area, calculated based on the smaller area of ​​the bottom electrode and the top electrode, unit m 2 ; d is the thickness of the standard piezoelectric material, unit: m;

[0047] Taking the diffraction peak intensity ratio of the effective crystal plane as the weight, the obtained standard relative dielectric constant as the dependent variable, and the theoretical dielectric constant of each crystal plane as the independent variable, the weighted average calculation equation group of the independent variables is listed, and the equations are solved jointly to obtain the theoretical dielectric constant of the crystal plane.

[0048] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0049] The method for nondestructively testing the relative dielectric constant of a piezoelectric material described in the present invention does not require additional top electrode and bottom electrode plating, thereby reducing detection costs and improving detection efficiency; does not require cutting or etching of wafers and films, is completely nondestructive, and the wafers and films after detection can be used for subsequent device preparation; can achieve in-plane multi-point detection, thereby evaluating the in-plane uniformity of the relative dielectric constant; the relative dielectric constant value obtained by the present invention has an error within 5% of the relative dielectric constant value measured by the parallel plate capacitor method, which fully meets actual needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is the XRD test spectrum of the PZT thin film wafer of Example 1;

[0051] Figure 2 is a relative dielectric constant result diagram of the PZT thin film wafer of Example 1 measured by the parallel plate capacitor method;

[0052] Figure 3 is the XRD test spectrum of the PZT thin film wafer of Example 2;

[0053] Figure 4 is a relative dielectric constant result diagram of the PZT thin film wafer of Example 2 measured by the parallel plate capacitor method;

[0054] Figure 5 is the XRD test spectrum of the PZT thin film wafer of Example 3;

[0055] Figure 6 is a relative dielectric constant result diagram of the PZT thin film wafer of Example 3 measured by the parallel plate capacitor method;

[0056] Figure 7 is the XRD test spectrum of the PZT thin film wafer of Example 4;

[0057] Figure 8 is a relative dielectric constant result diagram of the PZT thin film wafer of Example 4 measured by the parallel plate capacitor method;

[0058] Fig. 9 is the XRD test spectrum of the PZT thin film wafer of Example 5;

[0059] Fig.10 is a graph showing the relative dielectric constant of the PZT thin film wafer of Example 5 measured using a parallel plate capacitor method;

[0060] Fig.11 It is the XRD test spectrum of three groups of PZT thin film wafers with only perovskite phase (100) / (200) orientation;

[0061] Fig.12 This is a graph of the relative dielectric constant results of three groups of PZT thin film wafers with only the perovskite phase (100) / (200) orientation measured using the parallel plate capacitor method. DETAILED DESCRIPTION

[0062] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0063] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0064] Example 1

[0065] This embodiment provides a method for non-destructively testing the relative dielectric constant of a piezoelectric material, comprising the following steps:

[0066] Providing a piezoelectric material to be tested, wherein the piezoelectric material to be tested is a PZT thin film wafer prepared by a magnetron sputtering process, with a thickness of 1 μm, provided with a bottom electrode Pt, but no top electrode;

[0067] The PZT thin film wafer was tested by X-ray diffraction, and the obtained orientation and diffraction peak spectra are as follows: Figure 1 As shown, the peak at about 40° is the diffraction peak of the bottom electrode Pt (111) orientation, which does not belong to the PZT thin film wafer;

[0068] The phase that contributes to the relative dielectric constant of the piezoelectric material to be tested is determined to be the perovskite phase, and the crystal planes (100), (110), (111) and (211) of the perovskite phase are taken as effective crystal planes, and other crystal planes of the perovskite phase and the crystal planes of the pyrochlore phase are not calculated. The diffraction peak intensity of each effective crystal plane is obtained, and after the total diffraction peak intensity is obtained by summing, the diffraction peak intensity ratio of each effective crystal plane is calculated according to the following formula:

[0069]

[0070] Among them, R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl); P (hkl) is the diffraction peak intensity of the crystal plane (hkl); P (100) , P (110) , P (111) and P (211) are the diffraction peak intensities of the crystal planes (100), (110), (111) and (211);

[0071] Get R (100) , R (110) , R (111) and R (211) They are 2.24%, 78.46%, 15.07% and 2.86% respectively; according to the test experience (see below), the theoretical data of the relative dielectric constants of the four orientations of the perovskite phase (100), (110), (111) and (211) at 10kHz (i.e., the theoretical dielectric constants) are 1291, 270, 745 and 323 respectively;

[0072] Then, the weighted average of the theoretical dielectric constant of each effective crystal plane is calculated according to the following formula, taking the diffraction peak intensity ratio of the effective crystal plane as the weight:

[0073] ε r =∑R (hkl) *ε (hkl) ;

[0074] Among them, ε r is the relative dielectric constant; ε (hkl)represents the theoretical dielectric constant of the crystal plane (hkl); R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl);

[0075] Get the relative dielectric constant ε of the piezoelectric material to be tested r =362.

[0076] The PZT thin film wafer is cut and plated with the top electrode, and then tested using the parallel plate capacitor method, such as Figure 2 As shown, the actual relative dielectric constant obtained is 357, and the error with the method of non-destructively testing the relative dielectric constant of piezoelectric materials is 0.7%, which is within 5% and in line with expectations.

[0077] Example 2

[0078] This embodiment provides a method for non-destructively testing the relative dielectric constant of a piezoelectric material, comprising the following steps:

[0079] Providing a piezoelectric material to be tested, wherein the piezoelectric material to be tested is a PZT thin film wafer prepared by a magnetron sputtering process, with a thickness of 0.8 μm, provided with a bottom electrode Pt, but no top electrode;

[0080] The PZT thin film wafer was tested by X-ray diffraction, and the obtained orientation and diffraction peak spectra are as follows: Figure 3 As shown, the peak at about 40° is the diffraction peak of the bottom electrode Pt (111) orientation, which does not belong to the PZT thin film wafer;

[0081] The phase that contributes to the relative dielectric constant of the piezoelectric material to be tested is determined to be the perovskite phase, and the crystal planes (100), (110), (111) and (211) of the perovskite phase are taken as effective crystal planes, and other crystal planes of the perovskite phase and the crystal planes of the pyrochlore phase are not calculated. The diffraction peak intensity of each effective crystal plane is obtained, and after the total diffraction peak intensity is obtained by summing, the diffraction peak intensity ratio of each effective crystal plane is calculated according to the following formula:

[0082]

[0083] Among them, R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl); P (hkl) is the diffraction peak intensity of the crystal plane (hkl); P (100) , P (110) , P (111) and P (211) are the diffraction peak intensities of the crystal planes (100), (110), (111) and (211);

[0084] Get R (100) , R (110) , R(111) and R (211) They are 1.15%, 95.60%, 0.86% and 0.38% respectively. According to test experience, the theoretical data of relative dielectric constants of the four orientations of the perovskite phase (100), (110), (111) and (211) at 10kHz (i.e. theoretical dielectric constants) are 1291, 270, 745 and 323 respectively.

[0085] Then, the weighted average of the theoretical dielectric constant of each effective crystal plane is calculated according to the following formula, taking the diffraction peak intensity ratio of the effective crystal plane as the weight:

[0086] ε r =∑R (hkl) *ε (hkl) ;

[0087] Among them, ε r is the relative dielectric constant; ε (hkl) represents the theoretical dielectric constant of the crystal plane (hkl); R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl);

[0088] Get the relative dielectric constant ε of the piezoelectric material to be tested r =281.

[0089] The PZT thin film wafer is cut and plated with the top electrode, and then tested using the parallel plate capacitor method, such as Figure 4 As shown, the actual relative dielectric constant obtained is 286, and the error with the method of non-destructively testing the relative dielectric constant of piezoelectric materials is 0.9%, which is within 5% and in line with expectations.

[0090] Example 3

[0091] This embodiment provides a method for non-destructively testing the relative dielectric constant of a piezoelectric material, comprising the following steps:

[0092] Providing a piezoelectric material to be tested, wherein the piezoelectric material to be tested is a PZT thin film wafer prepared by a magnetron sputtering process, with a thickness of 0.6 μm, provided with a bottom electrode Pt, but without a top electrode;

[0093] The PZT thin film wafer was tested by X-ray diffraction, and the obtained orientation and diffraction peak spectra are as follows: Figure 5 As shown, the peak at about 40° is the diffraction peak of the bottom electrode Pt (111) orientation, which does not belong to the PZT thin film wafer;

[0094] The phase that contributes to the relative dielectric constant of the piezoelectric material to be tested is determined to be the perovskite phase, and the crystal planes (100), (110), (111) and (211) of the perovskite phase are taken as effective crystal planes, and other crystal planes of the perovskite phase and the crystal planes of the pyrochlore phase are not calculated. The diffraction peak intensity of each effective crystal plane is obtained, and after the total diffraction peak intensity is obtained by summing, the diffraction peak intensity ratio of each effective crystal plane is calculated according to the following formula:

[0095]

[0096] Among them, R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl); P (hkl) is the diffraction peak intensity of the crystal plane (hkl); P (100) , P (110) , P (111) and P (211) are the diffraction peak intensities of the crystal planes (100), (110), (111) and (211);

[0097] Get R (100) , R (110) , R (111) and R (211) They are 26.87%, 17.91%, 44.03% and 11.19% respectively; according to test experience, the theoretical data of the relative dielectric constants of the four orientations of the perovskite phase (100), (110), (111) and (211) at 10kHz (i.e., the theoretical dielectric constants) are 1291, 270, 745 and 323 respectively;

[0098] Then, the weighted average of the theoretical dielectric constant of each effective crystal plane is calculated according to the following formula, taking the diffraction peak intensity ratio of the effective crystal plane as the weight:

[0099] ε r =∑R (hkl) *ε (hkl) ;

[0100] Among them, ε r is the relative dielectric constant; ε (hkl) represents the theoretical dielectric constant of the crystal plane (hkl); R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl);

[0101] Get the relative dielectric constant ε of the piezoelectric material to be tested r =759.

[0102] The PZT thin film wafer is cut and plated with the top electrode, and then tested using the parallel plate capacitor method, such as Figure 6As shown, the actual relative dielectric constant obtained is 771, and the error with the method of non-destructive testing of the relative dielectric constant of piezoelectric materials is 0.8%, which is within 5% and in line with expectations.

[0103] Example 4

[0104] This embodiment provides a method for non-destructively testing the relative dielectric constant of a piezoelectric material, comprising the following steps:

[0105] Providing a piezoelectric material to be tested, wherein the piezoelectric material to be tested is a PZT thin film wafer prepared by a magnetron sputtering process, with a thickness of 0.5 μm, provided with a bottom electrode Pt, but no top electrode;

[0106] The PZT thin film wafer was tested by X-ray diffraction, and the obtained orientation and diffraction peak spectra are as follows: Figure 7 As shown, the peak at about 40° is the diffraction peak of the bottom electrode Pt (111) orientation, which does not belong to the PZT thin film wafer;

[0107] The phase that contributes to the relative dielectric constant of the piezoelectric material to be tested is determined to be the perovskite phase, and the crystal planes (100), (110), (111) and (211) of the perovskite phase are taken as effective crystal planes, and other crystal planes of the perovskite phase and the crystal planes of the pyrochlore phase are not calculated. The diffraction peak intensity of each effective crystal plane is obtained, and after the total diffraction peak intensity is obtained by summing, the diffraction peak intensity ratio of each effective crystal plane is calculated according to the following formula:

[0108]

[0109] Among them, R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl); P (hkl) is the diffraction peak intensity of the crystal plane (hkl); P (100) , P (110) , P (111) and P (211) are the diffraction peak intensities of the crystal planes (100), (110), (111) and (211);

[0110] Get R (100) , R (110) , R (111) and R (211) They are 27.08%, 45.83%, 4.17% and 18.75% respectively. According to test experience, the theoretical data of relative dielectric constants of the four orientations of the perovskite phase (100), (110), (111) and (211) at 10kHz (i.e. theoretical dielectric constants) are 1291, 270, 745 and 323 respectively.

[0111] Then, the weighted average of the theoretical dielectric constant of each effective crystal plane is calculated according to the following formula, taking the diffraction peak intensity ratio of the effective crystal plane as the weight:

[0112] ε r =∑R (hkl) *ε (hkl) ;

[0113] Among them, ε r is the relative dielectric constant; ε (hkl) represents the theoretical dielectric constant of the crystal plane (hkl); R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl);

[0114] Get the relative dielectric constant ε of the piezoelectric material to be tested r =565.

[0115] The PZT thin film wafer is cut and plated with the top electrode, and then tested using the parallel plate capacitor method, such as Figure 8 As shown, the actual relative dielectric constant obtained is 546, and the error with the method of non-destructively testing the relative dielectric constant of piezoelectric materials is 1.7%, which is within 5% and in line with expectations.

[0116] Example 5

[0117] This embodiment provides a method for non-destructively testing the relative dielectric constant of a piezoelectric material, comprising the following steps:

[0118] Providing a piezoelectric material to be tested, wherein the piezoelectric material to be tested is a PZT thin film wafer prepared by a magnetron sputtering process, with a thickness of 2 μm, provided with a bottom electrode Ti / Pt, but no top electrode;

[0119] The PZT thin film wafer was tested by X-ray diffraction, and the obtained orientation and diffraction peak spectra are as follows: Fig. 9 As shown, the peak at about 40° is the diffraction peak of the bottom electrode Pt (111) orientation, which does not belong to the PZT thin film wafer;

[0120] The phase that contributes to the relative dielectric constant of the piezoelectric material to be tested is determined to be the perovskite phase, and the crystal planes (100), (110), (111) and (211) of the perovskite phase are taken as effective crystal planes, and other crystal planes of the perovskite phase and the crystal planes of the pyrochlore phase are not calculated. The diffraction peak intensity of each effective crystal plane is obtained, and after the total diffraction peak intensity is obtained by summing, the diffraction peak intensity ratio of each effective crystal plane is calculated according to the following formula:

[0121]

[0122] Among them, R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl); P(hkl) is the diffraction peak intensity of the crystal plane (hkl); P (100) , P (110) , P (111) and P (211) are the diffraction peak intensities of the crystal planes (100), (110), (111) and (211);

[0123] Since there are only two types of orientations in the sample, (100) / (200) and (110), we get R (100) , R (110) They are 66.67% and 33.33% respectively. According to test experience, the theoretical data of the relative dielectric constants of the perovskite phase crystal plane (100) and (110) at 10kHz (i.e., the theoretical dielectric constants) are 1291 and 270 respectively.

[0124] Then, the weighted average of the theoretical dielectric constant of each effective crystal plane is calculated according to the following formula, taking the diffraction peak intensity ratio of the effective crystal plane as the weight:

[0125] ε r =∑R (hkl) *ε (hkl) ;

[0126] Among them, ε r is the relative dielectric constant; ε (hkl) represents the theoretical dielectric constant of the crystal plane (hkl); R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl);

[0127] Get the relative dielectric constant ε of the piezoelectric material to be tested r =951.

[0128] The PZT thin film wafer is cut and plated with the top electrode, and then tested using the parallel plate capacitor method, such as Fig.10 As shown, the actual relative dielectric constant obtained is 983, and the error with the method of non-destructively testing the relative dielectric constant of piezoelectric materials is 3.4%, which is within 5% and in line with expectations.

[0129] The theoretical data of the relative dielectric constants of the four orientations of the crystal plane (100), (110), (111), and (211) of the perovskite phase at 10 kHz (i.e., the theoretical dielectric constants) are 1291, 270, 745, and 323, respectively, which are obtained by the following method, taking the theoretical data of the relative dielectric constant of the crystal plane (100) of the perovskite phase as an example:

[0130] Three groups of PZT thin film wafers with only a (100) / (200) orientation of the perovskite phase are provided as standard piezoelectric materials, which are prepared by a magnetron sputtering process, have a thickness of 1.2 μm, are provided with a bottom electrode Pt, but no top electrode is provided;

[0131] The PZT thin film wafer was tested by X-ray diffraction, and the obtained orientation and diffraction peak spectra are as follows: Fig.11 As shown, it is verified that all three groups of samples are oriented in (100) / (200) direction, without other orientations, namely R (100) The proportion is 100%; the peak at about 40° is the diffraction peak of the bottom electrode Pt (111) orientation, which does not belong to the PZT thin film wafer;

[0132] Three groups of PZT thin film wafers were cut and plated with top electrodes, and then tested using the parallel plate capacitor method, such as Fig.12 As shown, the actual relative dielectric constants obtained are 1286 / 1328 / 1259, with an average value of 1291 and a fluctuation range of less than 3%, indicating that the data are reliable. Therefore, the average value of 1291 is used as the theoretical value of the relative dielectric constant of the (100) orientation.

[0133] Similarly, by preparing a PZT thin film wafer with only a single orientation, the theoretical data of the relative dielectric constants (i.e., theoretical dielectric constants) of the (110), (111), and (211) orientations at 10 kHz can be tested and calculated to be 270, 745, and 323, respectively.

[0134] From the above, it can be seen that the method of the present invention obtains different crystal planes (orientation distribution) that contribute to the relative dielectric constant in the piezoelectric material by means of X-ray diffraction, and the weighted average of the theoretical dielectric constants of each crystal plane is calculated by taking the diffraction peak intensity ratio of these crystal planes as weights to obtain the relative dielectric constant of the piezoelectric material. This method has a fast test speed, no need to prepare electrodes, each test point can be completed within 1 minute at the fastest, and there is no damage or pollution to the piezoelectric material. At the same time, it is convenient to test the relative dielectric constant at different positions on the entire piezoelectric wafer, and then evaluate the distribution uniformity of the relative dielectric constant in the plane.

[0135] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0136] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0137] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for non-destructively testing the relative dielectric constant of a piezoelectric material, characterized in that: The steps include: Perform an X-ray diffraction test on the piezoelectric material to be tested, determine the phase that contributes to the relative dielectric constant, obtain the diffraction peak intensity of each crystal plane of the phase, sum up to obtain the total diffraction peak intensity, and then calculate the diffraction peak intensity ratio of each crystal plane; The weighted average of the theoretical dielectric constants of each crystal plane is calculated using the diffraction peak intensity ratio of the crystal plane as the weight to obtain the relative dielectric constant of the piezoelectric material to be tested.

2. The method for nondestructively testing the relative dielectric constant of a piezoelectric material according to claim 1, characterized in that: Methods for obtaining the theoretical dielectric constant of a crystal plane include: In the piezoelectric material to be tested, determining the crystal planes used for calculation and the total number of crystal planes, and selecting a standard piezoelectric material corresponding to the total number; Performing an X-ray diffraction test on each of the standard piezoelectric materials to obtain the diffraction peak intensity of the corresponding crystal plane, summing up the total diffraction peak intensity, and then calculating the diffraction peak intensity ratio of the crystal plane; Using a parallel plate capacitor method, testing the standard relative dielectric constant of each of the standard piezoelectric materials; Taking the diffraction peak intensity ratio of the crystal plane as the weight, the obtained standard relative dielectric constant as the dependent variable, and the theoretical dielectric constant of the crystal plane as the independent variable, the weighted average calculation equation group of the independent variables is listed, and the equations are solved simultaneously to obtain the theoretical dielectric constant of the crystal plane.

3. The method for nondestructively testing the relative dielectric constant of a piezoelectric material according to claim 2, characterized in that: The parallel plate capacitor method includes: Bottom electrodes and top electrodes are prepared on both sides of the standard piezoelectric material to form a parallel plate capacitor. The capacitance value C of the obtained parallel plate capacitor is tested, and then the standard relative dielectric constant is calculated according to the following formula: C=(ε0×ε r ’×S) / d; Where C is the capacitance value, unit F; ε0 is the vacuum dielectric constant, ε0 = 8.85 × 10 -12 F / m; ε r ' is the standard relative dielectric constant; S is the electrode area, calculated based on the smaller area of ​​the bottom electrode and the top electrode, in units of m 2 ; d is the thickness of the standard piezoelectric material, unit: m.

4. The method for nondestructively testing the relative dielectric constant of a piezoelectric material according to claim 2 or 3, characterized in that: The test frequency of the parallel plate capacitor method is 1 kHz to 1 MHz.

5. The method for non-destructively testing the relative dielectric constant of a piezoelectric material according to any one of claims 1 to 4, characterized in that: The lowest index crystal plane in at least one crystal plane cluster in the phase is selected as the effective crystal plane, and only the effective crystal plane is used for calculation.

6. The method for nondestructively testing the relative dielectric constant of a piezoelectric material according to claim 5, characterized in that: The number of types of the crystal face clusters is 1, 2, 3 or 4.

7. The method for nondestructively testing the relative dielectric constant of a piezoelectric material according to any one of claims 1 to 6, characterized in that: The piezoelectric material to be tested includes a film or a wafer of polycrystalline lead zirconate titanate; the thickness of the piezoelectric material to be tested is 0.1 μm to 2 μm.

8. The method for nondestructively testing the relative dielectric constant of a piezoelectric material according to claim 7, characterized in that: The piezoelectric material to be tested is a film or wafer of polycrystalline lead zirconate titanate, and the contributing phase is a perovskite phase.

9. The method for nondestructively testing the relative dielectric constant of a piezoelectric material according to claim 8, characterized in that: The crystal planes of the perovskite phase include (100), (110), (111) and (211).

10. The method for non-destructively testing the relative dielectric constant of a piezoelectric material according to any one of claims 1 to 9, characterized in that: The steps include: A polycrystalline lead zirconate titanate film or wafer with a thickness of 0.1 μm to 2 μm is used as a piezoelectric material to be tested, and an X-ray diffraction test is performed on the piezoelectric material to be tested; the phase that contributes to the relative dielectric constant of the piezoelectric material to be tested is determined to be a perovskite phase, and the crystal planes (100), (110), (111) and (211) of the perovskite phase are used as effective crystal planes, and other crystal planes of the perovskite phase and the crystal planes of the pyrochlore phase are not calculated. The diffraction peak intensity of each effective crystal plane is obtained, and after the total diffraction peak intensity is obtained by summing, the diffraction peak intensity ratio of each effective crystal plane is calculated according to the following formula: Among them, R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl); P (hkl) is the diffraction peak intensity of the crystal plane (hkl); P (100) , P (110) , P (111) and P (211) are the diffraction peak intensities of the crystal planes (100), (110), (111) and (211); Taking the diffraction peak intensity ratio of the effective crystal plane as the weight, the weighted average of the theoretical dielectric constant of each effective crystal plane is calculated according to the following formula: e r =∑R (hkl) *e (hkl) ; Among them, ε r is the relative dielectric constant; ε (hkl) represents the theoretical dielectric constant of the crystal plane (hkl); R (hkl) is the diffraction peak intensity ratio of the crystal plane (hkl); Get the relative dielectric constant ε of the piezoelectric material to be tested r ; The method for obtaining the theoretical dielectric constant of the effective crystal plane includes: In the piezoelectric material to be tested, determining the effective crystal planes and the total number of effective crystal planes used for calculation, and selecting a standard piezoelectric material corresponding to the total number; Performing an X-ray diffraction test on each of the standard piezoelectric materials to obtain the diffraction peak intensity of the effective crystal plane, summing up the total diffraction peak intensity, and then calculating the diffraction peak intensity ratio of the effective crystal plane; Bottom electrodes and top electrodes are prepared on both sides of the standard piezoelectric material to form a parallel plate capacitor. The parallel plate capacitor method is used with a test frequency of 1kHz to 1MHz. The capacitance value C of the parallel plate capacitor obtained is tested, and then the standard relative dielectric constant of each standard piezoelectric material is calculated according to the following formula: C=(ε0×ε r ’×S) / d; Where C is the capacitance value, unit F; ε0 is the vacuum dielectric constant, ε0 = 8.85 × 10 -12 F / m; ε r ' is the standard relative dielectric constant, unit F / m; S is the electrode area, calculated based on the smaller area of ​​the bottom electrode and the top electrode, unit m 2 ; d is the thickness of the standard piezoelectric material, unit: m; Taking the diffraction peak intensity ratio of the effective crystal plane as the weight, the obtained standard relative dielectric constant as the dependent variable, and the theoretical dielectric constant of each crystal plane as the independent variable, the weighted average calculation equation group of the independent variables is listed, and the equations are solved jointly to obtain the theoretical dielectric constant of the crystal plane.

Citation Information

Cited By

  • Method for measuring light transmittance of glass substrate / piezoelectric film composite structure

    CN121633025A

  • Method for measuring light transmittance of glass substrate / piezoelectric thin film composite structure

    CN121633025B